Strut graft vs. traditional plating in the management of periprosthetic humeral fractures: a multicentric cohort study - Giuseppe Rollo; Michele Biserni; Gazi Huri; Christian Carulli; Mario Ronga; Michele Bisaccia; David Gomez-Garrido; Nezih Ziroglu; Enrico Maria Bonura; Andrea Alberto Ruberti; Andrea Schiavone; Luigi Meccariello (Medicinski glasnik, 2020)
Aim: The gradual increase in shoulder implants in active elderly patients has appeared in a parallel increase in periprosthetic humeral fractures. The aim of this study was to investigate the advantages of using strut grafting with plate fixation during periprosthetic humerus fractures. Methods: Thirty patients diagnosed with periprosthetic humeral fracture were divided into two groups. The first group of 15 patients (PS) underwent plate, ring, screws and strut allografts. The second group with resting 15 patients (PWS) was treated with only plate and screws. The criteria to evaluate the groups during followup were the Constant Shoulder Score (CSS) and Oxford Shoulder Score (OSS); the bone healing was measured by X-rays, controls measured by radiographic union score (RUS), and complications. The follow up was terminated at 12nd month in both groups. Results: The difference between the two groups in all parameters was not significant. However, all patients gained adequate shoulder motor skills for normal daily living activities. All fractures were healed. Only two complications were registered, and blood loss was minimal. Conclusion: We believe a revision to reverse shoulder prosthesis with a long-stem implant with or without cortical strut allograft augmentation to be safe and appropriate in the management of these complex injuries, though technically challenging, and having good results for normal activities daily life.
Keywords: bone strut; outcomes; bone healing; humeral; ORIF; periprosthetic